Comparison of a batch and flow approach for the lipase-catalyzed resolution of a Cyclopropanecarboxylate ester, a key building block for the synthesis of ticagrelor - Hugentobler, K; Rasparini, M; Thompson, L; Jolley, K; Blacker, A; Turner, N (American Chemical Society, 2016)
In this study a batch reactor process is compared to a flow chemistry approach for lipase-catalyzed resolution of the cyclopropanecarboxylate ester (±)-3. (1R,2R)-3 is a precursor of the amine (1R,2S)-2 which is a key building block of the API ticagrelor. For both flow and batch operation, the biocatalyst could be recycled several times, whereas in the case of the flow process the reaction time was significantly reduced.